49.7k views
2 votes
What is the solution to the equation 2(x-5)-9-3x+6+8+3x+6+8+3x+7???

2 Answers

1 vote

Simplifying

2(x + -5) = 9 + -3x + 6 + 8 + 3x + 7

Reorder the terms:

2(-5 + x) = 9 + -3x + 6 + 8 + 3x + 7

(-5 * 2 + x * 2) = 9 + -3x + 6 + 8 + 3x + 7

(-10 + 2x) = 9 + -3x + 6 + 8 + 3x + 7

Reorder the terms:

-10 + 2x = 9 + 6 + 8 + 7 + -3x + 3x

Combine like terms: 9 + 6 = 15

-10 + 2x = 15 + 8 + 7 + -3x + 3x

Combine like terms: 15 + 8 = 23

-10 + 2x = 23 + 7 + -3x + 3x

Combine like terms: 23 + 7 = 30

-10 + 2x = 30 + -3x + 3x

Combine like terms: -3x + 3x = 0

-10 + 2x = 30 + 0

-10 + 2x = 30

Solving

-10 + 2x = 30

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10' to each side of the equation.

-10 + 10 + 2x = 30 + 10

Combine like terms: -10 + 10 = 0

0 + 2x = 30 + 10

2x = 30 + 10

Combine like terms: 30 + 10 = 40

2x = 40

Divide each side by '2'.

x = 20

Simplifying

x = 20

User Pnuts
by
4.9k points
1 vote

The given expression is
2(x-5)=9-3x+6+8+3x+7


=2x-10=9-3x+6+8+3x+7

Combining all the like terms, we get,


=(2x+3x-3x)=(10+9+6+8+7)


=2x=40

Dividing both the sides of the equation by 2,

x=20 is the solution to the given equation.

User Sahil Mahajan Mj
by
4.8k points